Izkušenjsko učenje v slovenskih gimnazijah - Kolenc, Janez (Šolsko polje, 2006)
The majority of teachers today are aware, that the life-long learning and improving their teaching techniques and skills is an essential part of their profession. Namely, both teachers and students must learn from each other. Learning here means having the possibility of changing our behaviour on the experiential basis. In the process of learning we are getting knowledge, education, habits and skills and we can expand our emotional response in it aswell. Because of such an important role of learning we have decided to make a research on students' learning styles. The most frequently quoted model of learning styles is the model of experiential learning made by David Kolb. We have used this model of learning styles to investigate the relationship between learning and the self-concept of students. Several statistical analyses have been done for testing the hypothesis that students with higher self-concept areas in academics learn in a more complex way and easier and they have got better school grades as well.
Keywords: izkušenjsko učenje; gimnazije; učni stili; samopodoba; učni uspeh